THE INFLUENCE OF SPIRITUAL LEADERSHIP AND TEACHER COMPETENCE ON GRADUATE QUALITY MODERATED BY LEARNING ORGANIZATION CULTURE AT PESANTREN AL-AMIEN JEMBER - Miftahul Afkarina; Sutiah; Nurul Yaqien (SOSIOEDUKASI, 2025)
Graduate quality serves as the primary indicator of an educational institution’s success, including Islamic boarding schools (pesantren), which have a dual orientation: developing students’ academic competence and spirituality. The purpose of this study is to analyze the influence of spiritual leadership, teacher competence, and learning organization culture on graduate quality, as well as to examine the moderating role of learning organization culture in these relationships. This study employs a quantitative explanatory approach using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) method. The research population includes teachers, school principals, and students from four formal educational institutions under the auspices of Pesantren Al Amien Jember. The results reveal that: (1) spiritual leadership has a positive and significant effect on graduate quality (P-Value = 0.000); (2) teacher competence has a positive and significant effect on graduate quality (P-Value = 0.000); (3) learning organization culture has a positive and significant effect on graduate quality (P-Value = 0.018); (4) learning organization culture moderates the effect of spiritual leadership on graduate quality (P-Value = 0.010); and (5) learning organization culture also moderates the effect of teacher competence on graduate quality (P-Value = 0.032). These findings affirm that visionary spiritual leadership, excellent teacher competence, and an adaptive, collaborative learning organization culture play crucial roles in enhancing the quality of pesantren graduates. Practically, the results recommend the development of a sustainable learning culture within pesantren environments to produce graduates who are of strong character, globally competitive, and capable of contributing positively to society.